Developing Android-Based Teaching Modules Using MIT App Inventor - Ria Fakhrurriana (BATARA DIDI : English Language Journal, 2023)
Using android-based in the process of teaching and learning is one of attempts in elevating education quality. However, some teaching and learning sources are still paper based. This study was conducted to develop android-based teaching module for academic reading students in English Education Department. Applying RnD as research design, the researcher did data collection, preliminary study, need analysis, product construction, product implementation, evaluation, and product revision. The subject of this study is fourth semester students of IAIN Kediri majoring academic reading. After analyzing student's need and syllabus, the researcher designed the module three levels of exercise: easy, medium, and hard. This is aimed to know that the student’s proficiency is surely improved. The module was developed using MIT App Inventor. After that, the product was validated by expert and implemented on students. The result shows positive response. In summary, the android-based module for academic reading is appropriate to facilitate students in learning English for academic purposes, especially reading.